INTEGRATING EMOTIONAL INTELLIGENCE, SOCIAL INFLUENCE, AND VALUE ALIGNMENT IN SUSTAINABLE CONSUMER BEHAVIOR: EVIDENCE FROM GENERATION Z IN URBAN INDONESIA - Rumna Rumna; Hari Gursida; Doni Wihartika (Yayasan Education and Social Center, 2026)
This study examines the determinants of Sustainable Consumer Behavior (SCB) among Generation Z students in Bogor City, focusing on Emotional Intelligence (EI), Social Influence (SI), and Perceived Value Alignment (PVA). Using a quantitative, cross-sectional survey, 400 university students completed structured online questionnaires. Data were analyzed through SEM-PLS, assessing both measurement and structural models. Results indicate that Emotional Intelligence is the strongest predictor of SCB, followed by Perceived Value Alignment, while Social Influence exerts a smaller yet positive effect. The model explains 82.1% of the variance in SCB, demonstrating substantial predictive power. Discriminant validity assessments revealed high correlations among constructs, suggesting conceptual overlap. The study extends the Theory of Planned Behavior by integrating affective, value-based, and social dimensions in a post-digital context. Findings provide practical guidance for policymakers, marketers, and sustainability advocates in promoting sustainable consumption among digitally engaged youth